Feeding-induced hepatokines and crosstalk with multi-organ: A novel therapeutic target for Type 2 diabetes - Chen, Rong-Bin; Wang, Qi-Yu; Wang, Yuan-Yuan; Wang, Ya-Di; Liu, Jiang-Hua; Liao, Zhe-Zhen; Xiao, Xin-Hua (Frontiers in Endocrinology, 2023)
Hyperglycemia, which can be caused by either an insulin deficit and/or insulin resistance, is the main symptom of Type 2 diabetes, which is a significant endocrine metabolic illness.Conventional medications, including insulin and oral antidiabetic medicines, can alleviate the signs of diabetes, but they are unable to restore insulin release in a physiologically normal amount. The liver detects and reacts to shifts in nutritional condition that occur under a wide variety of metabolic situations, making it an essential organ for maintaining energy homeostasis. It also performs a crucial function in glucolipid metabolism through the secretion of hepatokines.Emerging research shows that feeding induces hepatokines releasing, which regulate glucose and lipid metabolism. Notably, these feeding-induced hepatokines act on multiple organs to regulate glucolipotoxicity and thus influence the development of T2DM.In this review, we focuses on describing how feeding-induced cross-talk between hepatokines, including Adropin, Manf, Leap2, and Pcsk9, and metabolic organs (e.g.brain, heart, pancreas, and adipose tissue) affects metabolic disorders, thus revealing a novel approach for both controling and managing of Type 2 diabetes as a promising medication.